Practical Cosmologies - Hoeppe, Götz (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2018)
For much of the 20th century, indigenous cosmologies, understood as the totalizing worldviews of delimited social groups, were one of ethnology’s central topics. In the last few decades, however, the concept of cosmology no longer sat well with many ethnologists’ wariness of identifying social wholes as analytic units and with accepting correspondences of social organization with orders of time, space, and color, among others. Recently, Allen Abramson and Martin Holbraad, in their 2014 book Framing Cosmologies, called for a “second wind” of anthropologists’ attention to cosmologies, now including popular understandings of Western science. While endorsing this broadened attention to cosmology and the uses of analyst’s perspectives, I call for remaining attentive to the practical uses of cosmologies by the actors that ethnographers learn from. This entails attending to the social accountabilities and organizational contexts that constrain how people act. I seek to illustrate this by drawing on ethnographies of fishers in south India as well as of astrophysicists in Germany.